Sintopy of two Tropidurus lizard species (Squamata: Tropiduridae) in a rocky Cerrado habitat in Central Brazil Sintopia de duas espécies de Tropidurus (Squamata: Tropiduridae) em um habitat de Cerrado rupestre no Brasil Central - R. G. Faria; A. F. B. Araujo (Brazilian Journal of Biology, 2004)
We studied the ecology of Tropidurus itambere and T. oreadicus that occur syntopically in rocky habitats of Cerrado vegetation in central Brazil during the dry season (April to September 2000). The two species are ecologically similar, but somewhat differentiated in vertical microhabitat use. The two species preferred rocky surface microhabitat. Both species demonstrated a unimodal activity pattern, with a peak between 10 and 15 h. Their diets were similar in composition and prey size. The most frequent item used by both species was ants, whereas the most important preys volumetrically were termites and ants. Small morphological differences observed between the two Tropidurus species could explain minor microhabitat divergence: T. itambere is slightly smaller, heavier, and more robust, and uses lower perches. T. oreadicus is larger, lankier, with longer extremities (tail, fore- and hindlegs), and uses a larger vertical microhabitat range. These ecological differences are slight, when compared with those observed between sympatric species of Tropidurus in spatially more heterogeneous landscapes. Considering the slight ecomorphological divergence between the two Tropidurus species and their high abundance in outcrops, we suggest that interspecific territoriality is the mechanism of coexistence. Estudamos a ecologia de Tropidurus itambere e T. oreadicus que ocorrem sintopicamente em habitats rochosos da vegetação de Cerrado, do Brasil Central, durante a estação seca (de abril até setembro de 2000). As duas espécies são ecologicamente similares, mas diferem no uso vertical do microhabitat, sendo a superfície das rochas o microhabitat mais usado pelas duas espécies. Ambas as espécies tiveram padrão de atividade unimodal, com pico entre as 10 e 15 h. Suas dietas foram similares na composição e tamanho de presa. O alimento mais freqüente das duas espécies de lagartos foi formiga, enquanto as presas volumetricamente mais importantes foram cupins e formigas. Pequenas diferenças morfológicas foram observadas entre as duas espécies de Tropidurus, que poderiam estar relacionadas ao uso do microhabitat. T. itambere é relativamente menor, mais pesado e robusto, usando poleiros mais baixos. T. oreadicus é maior, mais esguio, com extremidades mais longas (cauda, membros anteriores e posteriores), usando uma faixa vertical maior do microhabitat. Estas diferenças ecológicas são pequenas quando comparadas com as diferenças observadas entre espécies simpátricas de Tropidurus em paisagens espacialmente mais heterogêneas. Considerando a pequena divergência ecomorfológica entre as duas espécies de Tropidurus e sua alta abundância nos afloramentos, sugerimos que a territorialidade interespecífica é o mecanismo de coexistência.